Bioprospeksi Tumbuhan Obat Tradisional dalam Peningkatkan Potensi Obat Tradisional Berbasis Kearifan Lokal - Maidinia User; V. Susirani Kusumaputri; Tommy Hendrix (Balitbangda Provinsi Lampung, 2016)
Indonesia has a range of plant species that have the potential as a raw material of traditional medicine that had already used directly by the public. The development of traditional medicine is currently showing at a good stage, it is seen from the widespread use of herbal plants are used as commodities as drugs outside medical support. To obtain the value added benefits required bioprospecting stages so that utilization can take place in a sustainable manner and sustainable and can provide fair benefit sharing and the balance between the local community, governments, researcher, and industry. This study used a qualitative approach, the research data obtained from the literature and field studies with causality investigation system that is based observation of how the influence of bioprospeksi medicinal plants. Results indicate constraints experienced in bioprospecting activities require the regulation of access to biological resources, the concept of co-operation, monitoring and evaluation, science and technology dissemination to local communities, changing the working culture of local communities, implementation examples of technologies, and dissemination of regulations and policies to the local community. More information is needed in-depth study on bioprospecting system includes economic feasibility, availability of human resources, and the mechanism of action of bioprospecting.